KETERATURAN SOSIAL KEHIDUPAN MASYARAKAT PEDAGANG KAKI LIMA DI PASAR TAMAN AIR MOLEK - Adang Suherman (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2010)
Developed of city in third word so fast, and run together with rise of populations, and one of in Riau Province. The growth of populations not only concentrated in central city, like Pekanbaru, Dumai, but also in phery phery like Air Molek. One of the informal sector in Air Molek retailer. eventhough social regualarity has been there but to get regularity always confict, competition among retailer. thies research use descriptive methode, this research describe data from informan, interviewed and observed. the result of this research are 1) social regularity are value that recieve by servant community in Air Molek 2) If conflict rise among the servant, the rules of chief is more important, 3) Social regularity as norms, 4) Social awareness, 5) Have group responsibility